2015
DOI: 10.1088/0960-1317/26/1/015013
|View full text |Cite
|
Sign up to set email alerts
|

An optical microfluidic platform for spatiotemporal biofilm treatment monitoring

Abstract: Bacterial biofilms constitute in excess of 65% of clinical microbial infections, with the antibiotic treatment of biofilm infections posing a unique challenge due to their high antibiotic tolerance. Recent studies performed in our group have demonstrated that a bioelectric effect featuring low-intensity electric signals combined with antibiotics can significantly improve the efficacy of biofilm treatment. In this work, we demonstrate the bioelectric effect using sub-micron thick planar electrodes in a microflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A wide range of microscopic techniques, from confocal microscopy [ 145 ] and scanning electrochemical microscopy [ 146 ] to spectroscopic techniques [ 139 , 147 , 148 ], have been successfully coupled into microfluidic platforms for live observation of biofilm. Other techniques can also be integrated, such as the widely studied optical density for quorum sensing analysis [ 149 , 150 ] or the innovative use of electrochemical imaging, where specific positions of a voltammogram are converted into pixels, enabling identification of redox currents and peak positions of an electroactive biofilm [ 151 ]. The combination of microbial engineering approaches, including matter balance transformation, target microbe selection, mutant characterization, and microbial function analysis, with microfluidic BESs will provide really new information as is already a trend in other domains exploring the activity and behavior of microorganisms in microfluidic study systems [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of microscopic techniques, from confocal microscopy [ 145 ] and scanning electrochemical microscopy [ 146 ] to spectroscopic techniques [ 139 , 147 , 148 ], have been successfully coupled into microfluidic platforms for live observation of biofilm. Other techniques can also be integrated, such as the widely studied optical density for quorum sensing analysis [ 149 , 150 ] or the innovative use of electrochemical imaging, where specific positions of a voltammogram are converted into pixels, enabling identification of redox currents and peak positions of an electroactive biofilm [ 151 ]. The combination of microbial engineering approaches, including matter balance transformation, target microbe selection, mutant characterization, and microbial function analysis, with microfluidic BESs will provide really new information as is already a trend in other domains exploring the activity and behavior of microorganisms in microfluidic study systems [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidics involves the manipulation and control of a small amount of fluids in micrometer sized channels, which can be applied to understand the growth of biofilms on catheters via simulation of the local microenvironment [ 247 ]. Previous research utilizing microfluidics on biofilms include the study on biofilm formation and adhesion [ 248 ], effects of treatment [ 249 , 250 ], effects of synthetic QS [ 251 ], and effects of shear stress [ 252 ].…”
Section: Nanotechnology and Microtechnology In Antimicrobial Resismentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 102 ]. (For interpretation of the references to colour in this figure legend, the reader is referred to the Web version of this article.)…”
Section: Microsystems For Biofilm Studiesmentioning
confidence: 99%
“…Previous work conducted in our group showed that biofilm thickness can be determined using simple off-the shelf optoelectronic devices, such as photodiodes or CCD arrays, shown in Fig. 3 f–g [ 73 , 102 ]. Here, the optical density gives a direct measure of the biofilm thickness, while the CCD array functions in deriving the spatiotemporal thickness of the biofilms along the length of the channel.…”
Section: Microsystems For Biofilm Studiesmentioning
confidence: 99%